Analisis Penerapan Risiko dalam Penyusunan Portofolio Optimal - Arifin, Nisrina Putri; Mutasowifin, Ali (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
Investment is one of the determining variables and has a positive effect on economic growth (GDP). Investing in stocks with large market capitalization will increase JKSE growth. IDX80 is an index consisting of 80 stocks that have high liquidity, large market capitalization, and good company fundamentals. This study aims to find a combination of stocks that meet the criteria in forming an optimal portfolio based on the Markowitz model and the Single Index Model also to find the best portfolio performance using Value at Risk. This study uses reports of monthly stock price, JKSE, and interest rates BI7DRR period February 2019–February 2022. The results show there are 17 stocks combination form the optimal portfolio of the Single Index Model with an expected return of 0.01882 and a variance value of 0.002582 per month. While the optimal portfolio formed by the Markowitz model produces six stocks combination, the expected return and variance are 0.002243 and 0.003866 per month, respectively. Based on comparison using Value at Risk, the optimal portfolio by the Single Index Model is better than the Markowitz model because it has the highest expected return, the best risk, the lowest possible loss, and the best portfolio performance.